Variabel-variabel yang Memengaruhi Kejadian Fertilitas Remaja Perempuan Pernah Kawin di Daerah Perdesaan Indonesia Tahun 2022 - Aulia, Devira Sabrina; Setiadi, Yaya (Politeknik Statistika STIS, 2024)
Adolescent fertility is fertility that occurs in women aged 15-19 years (BKKBN, 2023). Fertility in adolescents has a higher risk of eclampsia, puerperal endometritis, and systemic infections than women aged 20-24 years (WHO, 2023). In addition, babies born to someone who is still a teenager are also greater at risk of premature birth, low birth weight, and neonatal death. In 2022, the incidence of adolescent fertility in rural areas (136,923 women) is higher than in urban areas (74,505 women). The purpose of this research is to determine the general description and analyze the variables that influence the incidence of adolescents fertility in ever-married women in rural Indonesia in 2022.. The analysis method used is binary logistic regression. Based on the results of data processing from Susenas March 2022, it shows that variables that significantly influence the incidence of adolescents fertility in rural areas are age at first marriage, poverty status, contraceptive use, and internet access.